ANALISIS PENGARUH KUALITAS PELAYANAN, FASILITAS KESEHATAN DAN WAKTU TUNGGU TERHADAP KEPUASAAN PASIEN RAWAT JALAN DI SATKES KODIKLATAL - Vanda Melynda Kabanga; Wasis Budiarto; Nugroho Mawardi (MAP (Jurnal Manajemen dan Administrasi Publik), 2023)
This study aims to analyze the influence of service quality, health facilities, and waiting times partially and simultaneously on out patient satisfaction in the Surabaya Clinical Health Unit.. This research was conducted with explanatory research and quantitative approaches.The location of this study was in the Surabaya Military Health Unit. The results of this study explain the quality of services and health facilities have a positive and significant effect on patient satisfaction in the polyclinic at Surabaya Military Health Unit. The waiting time has a negative and significant effect on patient satisfaction in the polyclinic Surabaya Military Health Unit.The quality of services, health facilities, and waiting times simultaneously had a significant effect on patient satisfaction in the polyclinic Surabaya Military Health Unit. The improvements in the quality of services and health facilities will improve patient satisfaction, but at an increasingly shorter waiting time it will also increase patient satisfaction in patient satisfaction at the Polyclinic Surabaya Military Health Unit.